Theoretical grounds for development of new generation state standards of vocational education - Luk’yanenko, G (Professional Pedagogics, 2011)
The article studies conceptual approaches as to vocational education and training modernization that are stipulated by socio-economic changes and swift development of market relations in the sphere of labor. The vocational education renovation demands reforming of both the model of qualified workers training, its transition from responding to advance and regulation basis viz standards of vocational training. According to the author, development of educational standards will be implemented on the basis of principles of solidity and flexibility, module-competence approach being the leading one